(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides detailed information on the infestation of carp (Cyprinus carpio L.) inhabiting the Zarafshan River in the Samarkand region with Philometroides nematodes (filometroidosis), the changes observed in infected fish, their biological characteristics, and the effects of this parasitic infestation on fish growth and development.